Sex differences during a cold-stress test in normobaric and hypobaric hypoxia: A randomized controlled crossover study - Hohenauer, Erich; Taube, Wolfgang; Freitag, Livia; Clijsen, Ron (Frontiers in Physiology, 2022)
Cold and hypoxia are two stressors that are frequently combined and investigated in the scientific literature. Despite the growing literature regarding normobaric hypoxia (NH) and hypobaric hypoxia (HH), responses between females and males are less often evaluated. Therefore, this study aims to investigate the physiological sex differences following a cold-stress test under normoxia, normobaric- and hypobaric hypoxia. A total of n=10 females (24.8±5.1yrs) and n=10 males (30.3±6.3yrs) from a university population volunteered for this study. The cold-stress test (CST) of the right hand (15°C for 2 min) was performed using a randomised crossover design in normobaric normoxia, NH and HH. The change (∆) from baseline to post-CST up to 15 min was analysed for cutaneous vascular conductance (CVC) and the hands’ skin temperature, whilst the mean values across time (post-CST up to 15 min) were assessed for peripheral oxygen saturation (SpO2), thermal sensation- and comfort. Pain pressure threshold (PPT) was assessed after the post-CST 15 min period. The hands’ skin temperature drop was higher (p=0.01) in the female group (∆3.3±1.5°C) compared to the male group (∆1.9±0.9°C) only in NH. Females (-0.9±0.5) rated this temperature drop in NH to feel significantly colder (p=0.02) compared to the males (-0.2±0.7). No differences were observed between sexes in NN, NH and HH for ∆CVC, SpO2, thermal comfort and PPT. In conclusion, females and males show similar reactions after a CST under normoxia and hypoxia. Sex differences were observed in the local skin temperature response and thermal sensation only in NH.